ANALISIS PENGARUH KEDISPLINAN KERJA, KEPUASAN KARYAWAN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN DI PT. DIAMOND COLD STORAGE - Trisna Trisna; Pamela Pamela; Saripudin Saripudin (ITB AAS Indonesia Surakarta, 2023)
This study aims to analyze the effect of work discipline, job satisfaction employees, and work motivation on the performance of the Production Division employees at PT Diamond Cold Storage. This study uses a quantitative descriptive analysis method with distributing questionnaires. The sample used in this study is an employee of PT Diamond Cold Storage of 100 people with the method Non Probability Sampling and data processed using the IBM SPSS application Version 25. Based on the results of the partial significance test (T-Test) the results obtained that (1) Work Discipline has a positive and significant effect on performance employees of PT Diamond Cold Storage; (2) Employee Satisfaction has an effect positive and no significant effect on employee performance of PT Diamond Cold Storage; (3) Work Motivation has a positive and significant effect on Employee Performance PT Diamond Cold Storage. Then the results of the simultaneous test (UjiF) state that work discipline, employee satisfaction, and work motivation together have a positive and significant effect on performance employees of PT Diamond Cold Storage. Key Words: Work Discipline, Employee Satisfaction, Work Motivation, Performance Employee